Sistem Informasi Pemeliharaan Meter Solusiefisien dalam Manajemen Alat Ukur di PLN Ranting Cabang Kisaran - Mhd Ridho Sirait (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Meter management and maintenance play a critical role in ensuring billing accuracy and operational efficiency at PLN, particularly in the Kisaran Branch Office. The manual system currently employed often encounters challenges such as inconsistent data recording, delays in maintenance, and a lack of information transparency. To address these issues, a Meter Maintenance Information System has been designed as an efficient solution for managing measuring instruments.This system is designed to support meter data recording, maintenance schedule monitoring, maintenance history logging, and real- time reporting of meter conditions. Utilizing web-based technology and a centralized database, the system integrates meter data from various locations, facilitating decision- making for technical staff. Implementation results indicate that the Meter Maintenance Information System can improve management efficiency by up to 40%, reduce recording errors, and accelerate the identification process of meter damage. Furthermore, the system supports operational cost efficiency by optimizing maintenance schedules. Thus, this system is expected to serve as a strategic step for PLN to enhance service quality for its customers.